Revisiting Trade-offs between Rubisco Kinetic Parameters - Flamholz, Avi I. (Biochemistry, 2019)
[Image: see text] Rubisco is the primary carboxylase of the Calvin cycle, the most abundant enzyme in the biosphere, and one of the best-characterized enzymes. On the basis of correlations between Rubisco kinetic parameters, it is widely posited that constraints embedded in the catalytic mechanism enforce trade-offs between CO(2) specificity, S(C/O), and maximum carboxylation rate, k(cat,C). However, the reasoning that established this view was based on data from ≈20 organisms. Here, we re-examine models of trade-offs in Rubisco catalysis using a data set from ≈300 organisms. Correlations between kinetic parameters are substantially attenuated in this larger data set, with the inverse relationship between k(cat,C) and S(C/O) being a key example. Nonetheless, measured kinetic parameters display extremely limited variation, consistent with a view of Rubisco as a highly constrained enzyme. More than 95% of k(cat,C) values are between 1 and 10 s(–1), and no measured k(cat,C) exceeds 15 s(–1). Similarly, S(C/O) varies by only 30% among Form I Rubiscos and <10% among C(3) plant enzymes. Limited variation in S(C/O) forces a strong positive correlation between the catalytic efficiencies (k(cat)/K(M)) for carboxylation and oxygenation, consistent with a model of Rubisco catalysis in which increasing the rate of addition of CO(2) to the enzyme–substrate complex requires an equal increase in the O(2) addition rate. Altogether, these data suggest that Rubisco evolution is tightly constrained by the physicochemical limits of CO(2)/O(2) discrimination.